2022
DOI: 10.1002/lary.30163
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Persistent Tracheocutaneous Fistula After Pediatric Tracheostomy Decannulation

Abstract: Objectives To determine the incidence of tracheocutaneous fistula (TCF) and identify characteristics associated with persistence. Study Design Prospective cohort. Methods All successfully decannulated children (<18 years) between 2014 and 2020 at a tertiary children's hospital were included. Revision tracheostomies, concomitant major neck surgery, or single‐stage laryngotracheal reconstructions were excluded. A persistent TCF was defined as a patent fistula at 6 weeks after decannulation. Results A total of 77… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
(82 reference statements)
0
5
0
Order By: Relevance
“…TCF is not uncommon in children. Our previous study and a recent study by Teplitzky et al report a 57%-65% rate of TCF in children following decannulation, with tracheostomy dependence over 2 years being an identified risk factor 2,7. Notably, in the Teplitzky et al article, 50 of 77 children developed a TCF and none of the patients underwent stomal maturation.…”
mentioning
confidence: 68%
“…TCF is not uncommon in children. Our previous study and a recent study by Teplitzky et al report a 57%-65% rate of TCF in children following decannulation, with tracheostomy dependence over 2 years being an identified risk factor 2,7. Notably, in the Teplitzky et al article, 50 of 77 children developed a TCF and none of the patients underwent stomal maturation.…”
mentioning
confidence: 68%
“…This is likely due to the inherent risk factors of the population. A recent study by Teplitzky et al found that early tracheostomy placement, duration of tracheostomy greater than 2 years, gestational age and chronic respiratory failure were each associated with an increased risk for TCF 18 . These conditions are almost universal among EP patients.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Teplitzky et al found that early tracheostomy placement, duration of tracheostomy greater than 2 years, gestational age and chronic respiratory failure were each associated with an increased risk for TCF. 18 These conditions are almost universal among EP patients. To the best of our knowledge, this is the first study to illustrate the increased incidence of TCF in postoperative patients with EP.…”
Section: Discussionmentioning
confidence: 99%
“…In patients decannulated following double-stage open airway reconstruction, the incidence has been found to be as high as 85% [34]. The most commonly identified risk factor related to TCF formation is duration of tracheostomy, with a cannulation period of over 24 months being most strongly correlated [31,32,33]. Two recent studies identified age at tracheostomy placement, as well as the presence of tracheobronchomalacia or congenital malformations as risk factors [32,33].…”
Section: Tracheocutaneous Fistulamentioning
confidence: 99%